Determinants of Carbon Dioxide Emissions in ASEAN-5 From 2010-2022: Though Energy Transition - Filda Luthfiana (Efficient: Indonesian Journal of Development Economics, 2025)
Economic activity and energy consumption are the main drivers of the increase in CO₂ emissions that trigger global climate change. This study analyzes the effect of GDP per capita, GDP per capita squared, renewable energy consumption, non- renewable energy consumption, and environmental taxes on CO₂ emissions in ASEAN-5 (Singapore, Malaysia, Thailand, Philippines, and Vietnam) for the period 2010-2022 using the FMOLS dynamic panel method. The results show that GDP per capita, renewable energy consumption, and non-renewable energy have a significant positive effect on CO₂ emissions, while environmental taxes and GDP per capita have a significant negative effect. This study supports the Environmental Kuznets Curve hypothesis in the long run. Policy recommendations include diversifying the low-emission economy, reducing non- renewable energy consumption, accelerating the adoption of renewable energy with incentives, and strengthening environmental taxes to encourage environmentally and human-friendly technologies.